2015
DOI: 10.17796/1053-4628-39.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Flexural and Microtensile Bond Strength of Bulk Fill Materials

Abstract: Within the limitations of this study, the use of a bonding agent without acid-etching showed positive interactions between base materials and composite resin and there were no significant differences in μTBS of these materials to dentin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…In this study, the specimen was sectioned to obtain sticks as the hourglass sample fails at lower stress comparing with the dumbbell or stick, because of the high stress concentration prompted in the adhesive (32&33) .The bonded area of specimens is small stick-shaped, about 0.1 mm 2 ± 0.1 which is important in producing better stress distribution at the adhesive joint, lowering cohesive failures in tooth substrate or composite (34) .In the present study, results showed that mean microtensile bond strength of packable (X-tra Fill) bulk fill composite is 23.98 MPa ± 7.954 MPa which is higher than the mean microtensile bond strength of flowable (X-tra Base) bulk fill composite 17.82 MPa ±7.814 MPa but with no statistically significant difference among the 2 groups. (P value =0.097).These findings agree with Öznurhan et al (35) , who reported that there were no significant variations in micro tensile bond strength of this bulk fill materials (SDR, X-tra base flowable bulk fill composites and TetricEvoCeram packable bulk fill composite) to dentin.While they come in partially disagreement with Al-Harbi et al (36) , who found that there is no significant variations in μTBS values among bulk fill resin composites (packable and flowable) and incremental composite, however, two bulk fill flowable resin composites (Smart Dentin Replacement flowable bulk fill composite and SonicFill) showed higher μTBS than the incremental resin composite. The difference in the materials might explain the variations in the results between studies.…”
Section: -Microtensile Bond Strengthsupporting
confidence: 89%
“…In this study, the specimen was sectioned to obtain sticks as the hourglass sample fails at lower stress comparing with the dumbbell or stick, because of the high stress concentration prompted in the adhesive (32&33) .The bonded area of specimens is small stick-shaped, about 0.1 mm 2 ± 0.1 which is important in producing better stress distribution at the adhesive joint, lowering cohesive failures in tooth substrate or composite (34) .In the present study, results showed that mean microtensile bond strength of packable (X-tra Fill) bulk fill composite is 23.98 MPa ± 7.954 MPa which is higher than the mean microtensile bond strength of flowable (X-tra Base) bulk fill composite 17.82 MPa ±7.814 MPa but with no statistically significant difference among the 2 groups. (P value =0.097).These findings agree with Öznurhan et al (35) , who reported that there were no significant variations in micro tensile bond strength of this bulk fill materials (SDR, X-tra base flowable bulk fill composites and TetricEvoCeram packable bulk fill composite) to dentin.While they come in partially disagreement with Al-Harbi et al (36) , who found that there is no significant variations in μTBS values among bulk fill resin composites (packable and flowable) and incremental composite, however, two bulk fill flowable resin composites (Smart Dentin Replacement flowable bulk fill composite and SonicFill) showed higher μTBS than the incremental resin composite. The difference in the materials might explain the variations in the results between studies.…”
Section: -Microtensile Bond Strengthsupporting
confidence: 89%
“…This chemical interaction between MDP and hydroxyapatite increase the mechanical strength of the adhesive interface in the self-etch strategy. (25) This agreement with Yoshida et al (26), Oznurhan et al in (16) whose found that with total-etch adhesive system the major elements that contribute to bond strength are intratubular resin-tag into demineralized intertubular dentine. This might be more difficult to happen in deep dentin because of the smaller amount of intertubular dentin to form the hybrid layer ,therefore deep dentin is more porous and retains more water within its enlarged tubule openings, which may avoid appropriate lateral bonding of the resin tags This disagreement with Ting et al (27) who reported that that the bond strength of one-step self-etch adhesive materials increased with increasing remaining dentin thickness (RDT), whereas that of two-step selfetch material was not affected by RDT.…”
Section: Effect Of Adhesive Systems and Dentin Level On Microtensile supporting
confidence: 75%
“…This lead to increase the translucency of resin composites and increase depth of cure with the aim to ensure that more photons penetrate into deeper areas of the material. (15) This confirmed by Oznurhan et al (16), Flury et al (17) whose found that the size of the filler particles of these materials may have an effect on their bond strength. Microscope images of these materials revealed that Xtra-Fill had the biggest particle size when compared with Tetric Bulk-fill and this might be the possible explanation of the higher bond strength values of these materials.…”
Section: Table (1): μ-Tensile Bond Strength Results (Mean Values ±Sd)mentioning
confidence: 54%
“…Nevertheless, results of the present systematic review revealed that the flexural strength of most flowable BF-RBCs were above the threshold defined by the ISO 4049 standard [ 12 ]. In addition, studies that also included in their experimental design high viscosity BF-RBCs found strength values in the same range of those displayed by the flowable BF-RBC [ 24 , 27 , 46 , 47 ]. For instance, no statistical differences in the flexural strength of X-tra Base (flowable) and X-tra fill (sculptable) were measured by Ilie et al.…”
Section: Discussionmentioning
confidence: 99%